An epidemiological cross sectional study to assess the prevalence of reproductive tract infections and sexually transmitted infections among married women in the reproductive age group in urban slum of Mumbai, Maharashtra, India - Rathod, Neeta D.; Akre, Charuhas V. (International Journal Of Community Medicine And Public Health, 2018)
Background: In developing countries reproductive tract infections (RTI) and sexually transmitted infections (STI) continue to present a major public health problem. Women in India had very low knowledge in sexually transmitted infections and HIV/AIDS. It is found that many of the RTI/STI is preventable and curable. The occurrence of STI/RTI among married women is quite high. Hence, this study will be carried out to assess prevalence of STI/RTI in the married women of reproductive age group in an urban slum. Methods: A cross-sectional study was carried out in the general OPD of Urban Health Centre, Mumbai during the period of 1st July 2015 to 31st July 2015. The data of 180 women in the reproductive age group of 15 to 49 years was collected by Pretested, semi structure interview schedule and statistically analyzed. Results: In the present study, the prevalence of STIs/RTIs symptoms was found to be 35.6%. Maximum prevalence of the symptoms among the study subjects found to be higher in the age group of 35 years and above (40.4%), in illiterate women (53.7%), women having one or two children (52.7%), women using IUD (50%) and women having per capita income <Rs. 5000/- (45.2%). Conclusions: There is a need for preventing new STI/RTI cases by educating people about the common symptoms, common methods of transmission, complications and preventive measures.